Peranan Keberadaan Bisnis Maklar Atau Perantara (Bimantara) Terhadap Penjual Dan Pembeli Ikan Di Pelabuhan Perikanan Banjarmasin Provinsi Kalimantan Selatan (Studi Kasus) - Darsani Darsani; Emmy Sri Mahreda; Emmy Lilimantik (EnviroScienteae, 2020)
This study aims to determine the role of the brokerage and intermediary business (BIMANTARA) in Banjarmasin Fishery Port at the fisher / producer level, at the buyer / consumer level, and the role in the buying and selling process of fishery products at the Banjarmasin Fishery Port, South Kalimantan Province. This research was conducted at the Banjarmasin Fishery Port with the object of research being fishermen / producers, buyers / consumers and intermediaries / brokers / agents, 40 samples were taken randomly. The data collected are primary data and secondary data. The data obtained were analyzed using qualitative descriptive analysis of the role of BIMANTARA at the fisherman / producer level, at the buyer / consumer level, and the role in the buying and selling process of fishery products at the Banjarmasin Fisheries Port, South Kalimantan Province. At the fisherman level / boat owners , BIMANTARA has several roles that are believed by fishermen / boat owners, including ensuring that the fish caught by fishermen can be sold out, being able to provide capital loans at sea, and providing security for transactions at the Banjarmasin Fishery Port. At the buyer / consumer level, BIMANTARA has several roles that are believed by buyers, including ensuring that they get the fish they want, being able to provide solutions for the cost of buying fish, and providing transaction security at the Banjarmasin Fishery Port. The role of BIMANTARA in the process of buying and selling fish caught at the Banjarmasin Fishery Port has a small effect on the determination of fish prices and sales and purchase permits, then it has a moderate effect on the provision of aid workers, but greatly affects the certainty of fish sales and fish purchases, is able to provide capital loans to buyers and sellers, and guarantee the security of the transaction of buying and selling fish caught at the Banjarmasin Fishery Port. Overall, the existence of BIMANTARA is needed by both sellers and buyers at the Banjarmasin Fishery Port.